Long Non-coding RNA KCNQ1OT1 Contributes to Antiepileptic Drug Resistance Through the miR-138-5p/ABCB1 Axis in vitro - Xie, Yangmei; Wang, Ming; Shao, Yiye; Deng, Xiaolin; Chen, Yinghui (Frontiers in Neuroscience, 2019)
Compelling evidence has verified that long noncoding RNAs (lncRNAs) play a critical role on drug resistance in various diseases, especially cancer. However, the role of lncRNAs underlying multidrug resistance in epilepsy remains to be clarified. In the present study, we investigated the potential regulatory mechanism of the lncRNA KCNQ1OT1 in regulating antiepileptic drug (AED) resistance in human brain microvascular endothelial cells (HBMECs). The results revealed that expression of P-glycoprotein (P-gp) and KCNQ1OT1 was significantly elevated in phenytoin-resistant HBMECs (HBMEC/PHT). Meanwhile, the activity of nuclear factor-kappa B (NF-κB) was increased in HBMECs/PHT cells. Microarray analysis indicated that miR-138-5p was downregulated in HBMEC/PHT cells. Interestingly, bioinformatics prediction tools indicated miR-138-5p could directly target the transcripts of KCNQ1OT1 and NF-κB/p65, and these results were confirmed by luciferase assays. Moreover, KCNQ1OT1 downregulation or miR-138-5p upregulation in vitro could inhibit P-gp expression and suppress NF-κB signaling pathway activation. Additionally, knockdown of KCNQ1OT1 or overexpression of miR-138-5p could increase the accumulation of rhodamine 123 (Rh123) and AEDs in HBMEC/PHT cells. Collectively, our results suggested that KCNQ1OT1 contributes to AED resistance through the miR-138-5p/NF-κB/ABCB1 axis in HBMEC/PHT cells, and these results provide a promising therapeutic target for the treatment of medically intractable epilepsy.